2020
DOI: 10.1007/s11127-020-00837-y
|View full text |Cite
|
Sign up to set email alerts
|

Voting for the underdog or jumping on the bandwagon? Evidence from India’s exit poll ban

Abstract: Exit poll surveys during elections are conducted to predict the outcome of actual elections. However, such polls historically have been controversial, particularly for multi-phase elections, because they can influence the behavior of voters in the later rounds of voting. If subsequent voters are more likely to vote for the predicted frontrunner, the effect is known as the bandwagon voting phenomenon, whereas if they vote for the predicted trailing candidate, the phenomenon is known as underdog voting. To avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Previous scholarship from elsewhere suggests that the effects we uncover here are not unique to Brazil and are likely to emerge in different types of political systems and contexts, including Britain (McAllister and Studlar 1991), France (Morton et al 2015), India (Chatterjee and Kamal 2020) and Israel (Riambau 2015). However, as we show, there are also characteristics that are specific to the Brazilian context, such as, for example, the impossibility of a bandwagon effect emerging from higher rates of turnout.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous scholarship from elsewhere suggests that the effects we uncover here are not unique to Brazil and are likely to emerge in different types of political systems and contexts, including Britain (McAllister and Studlar 1991), France (Morton et al 2015), India (Chatterjee and Kamal 2020) and Israel (Riambau 2015). However, as we show, there are also characteristics that are specific to the Brazilian context, such as, for example, the impossibility of a bandwagon effect emerging from higher rates of turnout.…”
Section: Discussionmentioning
confidence: 74%
“…Instead of a bandwagon effect, information exposure could also prompt the opposite: an ‘underdog effect’ – a less common prospect (Hardmeier 2008) that seems to be more likely in non-competitive elections (Chatterjee and Kamal 2020). Similarly to a bandwagon effect, the underlying mechanisms underpinning higher rates of support for the trailing candidate could also emerge from vote switching or changes in mobilization rates.…”
Section: Information Exposure and Voter Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular strong evidence comes from a recent study that used the asynchronous introduction of a ban on publishing polling information across various Indian states as a natural experiment. Results showed that support for trailing parties was higher if polling information was available, consistent with an underdog effect (Chatterjee & Kamal, 2021).…”
Section: Bandwagon Vs Underdog Effectsmentioning
confidence: 71%
“…1 Moreover, they may turn out to vote because of a longterm interest in maintaining democratic rule (Downs 1957, 267ff.). 2 Including the two-round presidential ballots of France (Blais 2004), the multiparty plurality contests of Canada (Schimpf 2019), India (Chatterjee and Kamal 2020) and the United Kingdom (Birch and Dennison 2019;Franklin, Niemi, and Whitten 1994;Kang 2004), the proportional system of the Netherlands (Van Spanje and Weber 2019), and the state-level elections of Germany (Kellermann 2008). 3 Using extant work as a prior, vote switching appears more likely than abstention.…”
Section: Notesmentioning
confidence: 99%